Age-Associated Dysregulation of Integrin Function in Vascular Smooth Muscle - Ojha, Krishna Raj; Shin, Song Yi; Padgham, Samuel; Leon Olmedo, Frida; Guo, Bohong; Han, Gang; Woodman, Christopher; Trache, Andreea (Frontiers in Physiology, 2022)
Arterial aging results in a progressive reduction in elasticity of the vessel wall and an impaired ability of aged blood vessels to control local blood flow and pressure. Recently, a new concept has emerged that the stiffening and decreased contractility of vascular smooth muscle (VSM) cells are important contributors to age-induced arterial dysfunction. This study investigated the hypothesized that aging alters integrin function in a matrix stiffness-dependent manner, which contributes to decreased VSM contractility in aged soleus muscle feed arteries (SFA). The effect of RGD-binding integrin blockade on contractile function of cannulated SFA isolated from young (4 months) and old (24 months) Fischer 344 rats was assessed by measuring constrictor responses of intact SFA to norepinephrine, phenylephrine, and angiotensin II. Results indicated that constrictor responses in presence of RGD were more impaired in old compared to young SFA. VSM cells isolated from young and old SFA were used for functional experiments using atomic force microscopy and high-resolution imaging. Aging was associated with a modulation of integrin β1 recruitment at cell-matrix adhesions that was matrix and substrate stiffness dependent. Our data showed that substrate stiffening drives altered integrin β1 expression in aging, while soft substrates abolish age-induced overall integrin β1 expression but show a matrix- and age-dependent spatial distribution. In addition, substrate stiffness and matrix composition contribute to the modulation of SMα-actin cytoskeleton architecture with soft substrates reducing age effects. Our results provide new insights into age-induced structural changes at VSM cell level that translates to decreased functionality of aged resistance soleus feed arteries.